High-Flow Nasal Cannula Oxygenation in Immunocompromised Patients With Acute Hypoxemic Respiratory Failure: A Groupe de Recherche Respiratoire en Réanimation Onco-Hématologique Study. Issue 3 (March 2017) - Lemiale, Virginie; Resche-Rigon, Matthieu; Mokart, Djamel; Pène, Frédéric; Argaud, Laurent; Mayaux, Julien; Guitton, Christophe; Rabbat, Antoine; Girault, Christophe; Kouatchet, Achille; Vincent, François; Bruneel, Fabrice; et al.
Abstract : Objective: In immunocompromised patients with acute respiratory failure, invasive mechanical ventilation remains associated with high mortality. Choosing the adequate oxygenation strategy is of the utmost importance in that setting. High-flow nasal oxygen has recently shown survival benefits in unselected patients with acute respiratory failure. The objective was to assess outcomes of immunocompromised patients with hypoxemic acute respiratory failure treated with high-flow nasal oxygen. Design: We performed a post hoc analysis of a randomized controlled trial of noninvasive ventilation in critically ill immunocompromised patients with hypoxemic acute respiratory failure. Setting: Twenty-nine ICUs in France and Belgium. Patients: Critically ill immunocompromised patients with hypoxemic acute respiratory failure. Intervention: A propensity score–based approach was used to assess the impact of high-flow nasal oxygen compared with standard oxygen on day 28 mortality. Measurements and Main Results: Among 374 patients included in the study, 353 met inclusion criteria. Underlying disease included mostly malignancies ( n = 296; 84%). Acute respiratory failure etiologies were mostly pneumonia ( n = 157; 44.4%) or opportunistic infection ( n = 76; 21.5%). Noninvasive ventilation was administered to 180 patients (51%). Invasive mechanical ventilation was ultimately needed in 142 patients (40.2%). Day 28 mortality was 22.6% (80 deaths). Throughout the ICU stay, 127 patients (36%) received high-flow nasal oxygen whereas 226 patients received standard oxygen. Ninety patients in each group (high-flow nasal oxygen or standard oxygen) were matched according to the propensity score, including 91 of 180 (51%) who received noninvasive ventilation. High-flow nasal oxygen was neither associated with a lower intubation rate (hazard ratio, 0.42; 95% CI, 0.11–1.61; p = 0.2) nor day 28 mortality (hazard ratio, 0.80; 95% CI, 0.45–1.42; p = 0.45). Conclusions: In immunocompromised patients with hypoxemic acute respiratory failure, high-flow nasal oxygen when compared with standard oxygen did not reduce intubation or survival rates. However, these results could be due to low statistical power or unknown confounders associated with the subgroup analysis. A randomized trial is needed. Abstract : Supplemental Digital Content is available in the text.